Funcionalidad familiar en el desempeño académico en estudiantes del cuarto grado de secundaria Institucion educativa primario secundario Nº60092 “PMA” el estrecho, Provincia Putumayo – 2023 - Vásquez Sisley, Héctor Miguel (2024)
The purpose of the research work was to determine family functionality before academic performance. The type of study was an applicative quasi- experimental design with pretest and posttest. The population consisted of 105 students enrolled in the 4th grade of secondary school at the I.E.P.S. Nº60092 "PMA" El Estrecho, Putumayo Province" registered during the year 2023, the sample size was 22 students. The survey/questionnaire was used as a data collection instrument. A descriptive process and an inferential process were used to analyze and interpret the data. It was concluded that when contrasting the before and after in the same study sample and without missing data the minimum difference between the before and after of 13,000 in the maximum is 18,000 and a mean difference of 15,773 which means that there is an appreciation of good before and after of the Family Functionality in the Academic Performance.